ڕۆڵى بەهاى ئاينى لەسەر شوناسى گەنجان توێژینەوەیەکى مەيدانيە لە هەرێمى کوردستان- عێراق - صابر, پ.د. نيان نامق; أحمد, م.ى. نەبەز أزور (Sulaimani Journal for Humanities, 2024)
This study aims to determine the statistical difference between religious values and youth identity according to the variables (age, gender) and to show the relationship between religious values in determining youth identity. The research is quantitative, and the descriptive method and method (social survey) of the type (descriptive survey) were used. The research community is young people living in the Kurdistan Region who are between (18-35) years old). The sample consisted of 472 youths randomly selected from the study community. The study results show that religious values change with age, and the younger the age, the higher the religious values, but there is no difference in gender. Youth identity changes with age but does not change with gender, and there is a strong relationship between religious values and youth identity.
Keywords: (Youth; Values; Religious Values; Value System; Identity)